Descomposición de la compensación por inflación y riesgo inflacionario en México - Ana María Aguilar-Argaez; Rocio Elizondo; Jessica Roldán-Pe\~na (Banco de México, 2016)
– This document studies the recent evolution of the break-even-inflation implicit in the yields of long-term financial instruments in Mexico. In particular, it analyzes the dynamics of its main components: the long-run inflation expectation and the inflationary risk premium, which are estimated by means of an affine term structure model of interest rates. The results show that the gradual reduction registered in such compensation in the last years is the result of the decrease showed by both components. This reflects, on the one hand, the progressive convergence of the estimated inflation expectation to Banco de México's inflation target as well as its anchoring and, on the other hand, that nominal-bond holders have required a lower hedging against future inflation, possibly, as a reflection of a lower risk perception associated to it.
Keywords: E31; E43; E52; G12; 330; Inflation; Break-even-inflation; Inflation expectation; Inflationary risk premium